TANTANGAN PEMBELAJARAN BERDIFERENSIASI DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN KUIN UTARA 1 - Salsa Bella, Ainun; Norhafizah; Nurhaliza, Siti; Maisarah , Sri; Ayu Pratiwi , Diani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted to identify the challenges and strategies of teachers in implementing differentiated learning as part of the Merdeka Curriculum at SDN Kuin Utara 1. The background of the issue lies in the diversity of students' learning styles, namely auditory, visual, and kinesthetic, which require different approaches in the learning process. This study employed an in-depth interview method with two educators as the main informants. The findings revealed that teachers faced challenges such as limited learning facilities, including teaching media and teaching aids, technological skill gaps among senior teachers, and insufficient in-depth training related to differentiated learning. The strategies implemented included initial evaluations of students' learning styles, the integration of teacher learning communities (Kombel), and the implementation of project-based learning (P5). Teachers also emphasized the importance of collaboration between younger and senior teachers in overcoming technological challenges. The conclusion of this research highlights the need for face-to-face training support and improved facilities to ensure the effective and sustainable implementation of the Merdeka Curriculum.